An optimized double-integral-sliding-mode-controller for a PV microgrid. Issue 5 (27th September 2021) - Pradhan, Swati Sucharita; Pradhan, Raseswari; Subudhi, Bidyadhar
Abstract : Purpose: The dynamics of the PV microgrid (PVMG) system are highly nonlinear and uncertain in nature. It is encountered with parametric uncertainties and disturbances. This system cannot be controlled properly by conventional linear controllers. H − controller and sliding mode controller (SMC) may capable of controlling it with ease. Due to its inherent dynamics, SMC introduces unwanted chattering into the system output waveforms. This paper aims to propose a controller to reduce this chattering. Design/methodology/approach: This paper presents redesign of the SMC by modifying its sliding surface and tuning its parameters by employing water-evaporation-optimization (WEO) based metaheuristic algorithm. Findings: By using this proposed water-evaporation-optimization algorithm-double integral sliding mode controller (WEOA-DISMC), the chattering magnitude is diminished greatly. Further, to examine which controller between H8 controller and proposed WEOA-DISMC performs better in both normal and uncertain situations, a comparative analysis has been made in this paper. The considered comparison parameters are reference tracking, disturbance rejection and robust stability. Originality/value: WEO tuned DISMC for PVMG system is the contribution.